DESAIN KEGIATAN EKSTRA KEAGAMAAN SEKOLAH DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA - Moch. Holilurrohman (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
Abstract This study discusses the design of extra-school religious activities in forming religious-character students at SMPN 31 Surabaya. The objectives of this study are: 1) To find out the school's efforts in forming religious character students at SMPN 31 Surabaya; 2) To find out what are the extra-religious activities of the school in forming students of religious character at SMPN 31 Surabaya; 3) To find out the supporting and inhibiting factors in designing extra-school religious activities in forming religious-character students at SMPN 31 Surabaya. This study includes research that uses a qualitative descriptive research approach and type. The data collection techniques used by researchers in this study were observation, interviews and documentation. The data analysis technique in this research is to use qualitative descriptive methods. From the research conducted by researchers, the results obtained are that the school's strategy in forming students of Surabaya's religious character is carried out in several ways both during learning activities and outside of school hours or religious extracurricular activities. What are the extra-religious activities of the school in forming students of religious character are Dhuha prayer in congregation, Prayer together before starting lessons, obligatory prayer in congregation, istighotsah together, reading and writing programs of the Koran, Islamic holidays, Friday program 'at sharing. As for the supporting and inhibiting factors in these activities, of course there are such as there are still some students who do not participate in the activity and also some inadequate infrastructure.